Acute myeloid leukemia with NPM1 mutation and favorable European LeukemiaNet category: outcome after preemptive intervention based on measurable residual disease. (8th June 2020) - Bataller, Alex; Oñate, Guadalupe; Diaz‐Beyá, Marina; Guijarro, Francesca; Garrido, Ana; Vives, Susana; Tormo, Mar; Arnan, Montserrat; Salamero, Olga; Sampol, Antònia; Coll, Rosa; Vall‐Llovera, Ferran; et al.
Summary: In the European LeukemiaNet favourable risk category, allogeneic haematopoietic stem cell transplantation (alloSCT) is not indicated in first complete remission for patients with acute myeloid leukaemia (AML) with NPM1 mutations (ELNfav NPM1 AML), although a proportion of these patients will relapse. Given the prognostic importance of measurable residual disease (MRD), CETLAM‐12 considered a pre‐emptive intervention in patients with molecular failure (MF). We analyzed 110 ELNfav NPM1 AML patients achieving complete remission (CR) after induction chemotherapy. Two‐year cumulative incidence of relapse (CIR), overall survival (OS) and leukaemia‐free survival (LFS) were 17%, 81·5% and 82%, respectively. Forty‐six patients required additional therapy for MF ( n  = 33) or haematological relapse (HemR; n  = 13), resulting in a molecular LFS (molLFS) and a cumulative incidence of MF at two years of 61% and 38% respectively. Two‐year OS for these 46 patients was 66%, with a different outcome between patients with MF (86%) and HemR (42%) ( P  = 0·002). Quantitative NPM1 detection at different timepoints was predictive of molLFS; an MRD ratio ( NPM1 mut/ ABL1  × 100) cut‐off of 0·05 after first consolidation identified two cohorts with a two‐year molLFS of 77% and 40% for patients below and above 0·05, respectively. In conclusion, MRD‐based pre‐emptive intervention resulted in a favourable outcome for ELNfav NPM1 AML patients.